Mobility, Risk and Adaptability of the Diaspora Merchants: The Case of the Sifneo Frères Family Firm in Taganrog (Russia), Instanbul and Piraeus, 1850-1940 - Sifneos, Evridiki (The Historical Review/La Revue Historique, 2011)
No abstract